Determination of the effect of pyocyanin and Saccharomyces boulardii on gut microbiota and TLR4/MyD88/NF-κB and NLRP3 signaling pathways in sepsis induced by cecal ligation and puncture in rats - Mahmut Ucar; Ozgur Celebi; Demet Celebi; Sumeyye Baser; Mustafa Can Guler; Ayhan Tanyeli; Metin Kılıclıoglu; Ahmet Yılmaz; Serkan Yıldırım (BMC Infectious Diseases)
Abstract Sepsis is a life-threatening systemic inflammatory condition marked by a dysregulated host response to infection. The intestinal microbiota plays a pivotal role in maintaining immune homeostasis and epithelial barrier integrity, whereas dysbiosis significantly contributes to the pathogenesis of sepsis. This study investigates the effects of the Pseudomonas aeruginosa-derived metabolite Pyocyanin and the probiotic Saccharomyces boulardii (S. boulardii) on microbial composition and the TLR4/MyD88/NF-κB/NLRP3 signaling axis in a cecal ligation and puncture (CLP)-induced rat model of sepsis. The experimental design assessed the synergistic or antagonistic effects of single and combined treatments using molecular, microbiome, and immunohistochemical parameters to evaluate histopathological damage and microbial ecological dynamics. Seven experimental groups were established following CLP. Intra-abdominal Pyocyanin (10 nmol/g) and oral probiotic (10⁶ CFU/kg) treatments were administered either individually or in combination. Focused Ion Beam - Scanning Electron Microscopy (FIB-SEM) analyses revealed that the amorphous structure of Pyocyanin interacted with the surface of S. boulardii. Western blot analysis showed a 2.3-fold increase in TLR4/NF-κB expression in the CLP group (p ≤ 0.05), which synergistically rose to 4.5-fold with Pyocyanin (p ≤ 0.001), whereas probiotic treatment decreased expression levels by 35%. According to 16 S rRNA sequencing, Pyocyanin reduced α-diversity by increasing Lactobacillaceae abundance to 32.66% (Shannon index: 3.598 vs. 4.433 in control), while S. boulardii enhanced β-diversity by elevating Coriobacteriaceae (5.85%) and Prevotellaceae (10.63%) levels (Tables 2, 3 and 4). PCoA confirmed 41.7% Bray-Curtis dissimilarity between groups at the species level (PERMANOVA R²=0.38, p = 0.002). Histopathologically, severe hepatocyte necrosis (73.2 ± 6.1%, p = 0.0022) and a 4.2-fold increase in hepatic TGF-β expression were observed in the CLP group, whereas epithelial barrier damage was significantly attenuated in the probiotic groups. Immunofluorescence analysis revealed that combined treatment reduced Caspase-8 and TLR4 expression by 28% compared to Pyocyanin alone (p ≤ 0.05). In conclusion, S. boulardii supported microbiota homeostasis by suppressing TLR4/NF-κB signaling, whereas Pyocyanin exacerbated the inflammatory response via NLRP3 activation. These findings provide molecular evidence supporting probiotic-assisted immunomodulatory strategies in sepsis therapy.